A new Hippeastrum (Amaryllidaceae) species from Brazil - Oliveira, Renata S.; Urdampilleta, Juan D.; Dutilh, Julie H.a. (Phytotaxa, 2017)
The largest genus of Amaryllidaceae in Brazil is Hippeastrum Herbert (1821: 31), with about 30 species and the widest geographical distribution in the country. The whole genus has about 60 species with two centers of diversity, Bolivia/Peru and Southeast/Southern Brazil (Meerow & Snijman 1998).